Gender-sensitive risks and options assessment for decision making (ROAD) to support WiF2 - Ringler, Claudia; Abdulrahim, Sawsan; Adra, May; Alvi, Muzna; Choudhury, Zahid ul Arefin; ElDidi, Hagar; Kilby, Patrick; Nassif, Gabriella; Ratna, Nazmun N.; Sufian, Farha D.; van Biljon, Chloe; Wu, Joyce (Centre of Excellence for Development Impact and Learning, 2023)
The Gender-Sensitive Risks and Options Assessment for Decision Making (ROAD) to Support WiF-2 (ROAD migration project), a partnership coordinated by the International Food Policy Research Institute (IFPRI), Australian National University, American University Beirut, Lincoln University, and University of Dhaka, evaluated the ILO-DFID Partnership Programme on Fair Recruitment and Decent Work for Women Migrant Workers in South Asia and the Middle East (Work in Freedom, Phase 2 project [WiF-2]), which operated from 2018 to 2023. The WiF-2 project specifically aimed “to reduce vulnerability to trafficking and forced labour of women and girls across migration pathways leading to the care sector and textiles, clothing, leather and footwear industries (TCLFI) of South Asia and Arab States” (ToC WiF-2). In this context, the International Labour Organization (ILO) describes three dimensions to forced labour: (i) unfree recruitment; (ii) work and life under duress; and (iii) impossibility to leave employer. Forced labour exists if any one of these dimensions exists. Exploitation relates to one or all of the following three elements: (i) restricting freedom of movement; (ii) economic exploitation; and (iii) violence or the threat of violence. Trafficking relates to migrants’ interactions with a network of individuals who organize the migration process, including brokers in origin countries and employment agencies, as well as employers in destination countries, with elements of deception, coercion, debt bondage, and slavery-like conditions. Trafficking also includes involuntary child labour. To address women and girl’s vulnerability to forced labour, exploitation, and trafficking, the WiF-2 program implemented pre-migration outreach interventions in countries of origin (Bangladesh, India, and Nepal). At the micro-level, this included training of a group of social workers who would engage women, girls, and other community members in countries of origin through door-to-door visits, community/courtyard meetings, and orientation events, and by providing referrals for vocational training.